2018
DOI: 10.5455/ijmsph.2018.0718917122017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of school absenteeism: A community-based study among children aged 7-18 years in a slum of Kolkata

Abstract: Background: Education is one of the basic needs for human development and going to school regularly is crucially important for advancement of a student's academic and social skills. Objectives: The main purpose of this study was to assess the magnitude and causes of school absenteeism and analyze the predictors of absenteeism among children in a slum community of Kolkata. Materials and Methods: A cross-sectional, community-based study was conducted in a slum of Chetla, Kolkata, where 192 subjects were surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…Apart from these, Amalu and Abang (2016) stated that financial constraints, lack of interest, illnesses, pampering from family members, location of school were the major causes of absenteeism among pupils. Similar findings are reported by Ghosh et al (2017) that the chief reasons for irregularity of students were illness (18.98%), rainy days (16.45%), and social or family occasions (11.28%). Senyametor et al (2018) reflected that 71.4 percent of absenteeism was due to teachers' inability to care the pupils, while 70 percent of teachers indicated lack of parental care was the major cause of absenteeism of students.…”
Section: Rationale Of the Studysupporting
confidence: 87%
See 1 more Smart Citation
“…Apart from these, Amalu and Abang (2016) stated that financial constraints, lack of interest, illnesses, pampering from family members, location of school were the major causes of absenteeism among pupils. Similar findings are reported by Ghosh et al (2017) that the chief reasons for irregularity of students were illness (18.98%), rainy days (16.45%), and social or family occasions (11.28%). Senyametor et al (2018) reflected that 71.4 percent of absenteeism was due to teachers' inability to care the pupils, while 70 percent of teachers indicated lack of parental care was the major cause of absenteeism of students.…”
Section: Rationale Of the Studysupporting
confidence: 87%
“…The study found that the majority of students do not attend school during harvesting season, rainy season and after long vacations. This result is supported by Ghosh et al (2017), Sahin and Arseven (2016).…”
Section: Discussionsupporting
confidence: 61%